(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The research was conducted within the framework of a new scientific field known as "investor relations" or "Investor Relations." This article explores the terminology systems of Investor Relations in both Russian and English, providing a comparative analysis of hypernymic and hyponymic relationships based on the thematic group "Nomination of persons associated with Investor Relations" in the two languages. The primary research methods employed include component and definitional analysis, as well as descriptive and semantic-logical approaches. The study emphasizes the concept of “investor relations” and examines examples of terms and terminological combinations in both Russian and English: инвестор, аналитик, акционер, директор, брокер, менеджер; investor, analyst, shareholder, director, broker, manager. The comparative analysis of this thematic group reveals distinctive characteristics of the hypernymic and hyponymic connections within the studied terminology, demonstrating a high degree of similarity in the structural organization and logical coherence of the terminology in both languages. The findings of this research are valuable not only for linguists but also for investor relations specialists, employees of financial and investment companies, and banks, contributing to effective communication in professional and business contexts.